2009
DOI: 10.1002/anie.200805307
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of N‐Acylcarbamates and N‐Acylsulfonamides Catalyzed by a Bifunctional [Cp*Ru(PN)] Complex

Abstract: Awakening of the Cp one: The bifunctional complex 1 facilitates the interaction with substrates bearing less electrophilic carbon atoms than ketones, epoxides, and imides. The title reaction was applicable to the reduction of Evans' asymmetric alkylation products to the chiral alcohols along with good recovery of the chiral oxazolidinone auxiliary. EWG = electron-withdrawing group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…by Ito et al (2011), Ito et al (2009), Ito et al (2007), Ito et al (2005), Ito et al (2003). Surprisingly, only a scarce number of corresponding Fe(II) complexes has been reported, e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…by Ito et al (2011), Ito et al (2009), Ito et al (2007), Ito et al (2005), Ito et al (2003). Surprisingly, only a scarce number of corresponding Fe(II) complexes has been reported, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…For related ruthenium complexes, see: Ito et al (2003Ito et al ( , 2005Ito et al ( , 2007Ito et al ( , 2009Ito et al ( , 2011. For corresponding Fe(II) complexes, see: Davies et al (1994); Lagaditis et al (2010).…”
Section: Related Literaturementioning
confidence: 99%
“…(Scheme a) . Due to the low electrophilicity of the carbonyl group of lactam, the reductive cleavage of inert C−N with H 2 is considered a very challenging task and usually occurs at elevated pressures, high reaction temperatures, and extended reaction time in the presence of strong bases (usually potassium tert ‐butoxide or potassium hexamethyl disilazane). From an environmental point of view, it would be practical and convenient to produce amino alcohols under neutral, or at least weakly alkaline, reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[3] In contrast, homogeneous catalytic hydrogenation of amides can performed under milder conditions, but most of the reported examples produced am ixture of alcohols and lower amines. [4] Ab reakthrough was made in 2007 by Cole-Hamiltone tal., who introduced the ruthenium complex of the Triphos ligand (1,1,1-tri(diphenylphosphinomethyl)ethane) into the hydrogenationo fN-phenyl amide to secondary amine with excellent selectivity,b ut relatively harsh reactionc onditions (164 8C, 40 bar;o r 210 8C, 10 bar) are required. [5] Recently,K lankermayer et al modified the Triphos ligand and found that ruthenium complexes of Xyl-Triphos ligands containing 3,5-dimethylphenyl groups have higha ctivity and selectivity for the hydrogenation of lactams to cyclic amines in the presence of ac atalytic amount of methanesulfonic acid as ac o-catalyst.…”
mentioning
confidence: 99%
“…The results summarized in Ta ble 2s how that all N-arylacetamides (1a-l) give high yields (80-95 %) and excellent CÀO/CÀNs electivities (12:1-38:1). The substituents on the phenyl ring of the substrates had little effect on the yield and selectivity of the reaction (entries [1][2][3][4][5][6][7][8][9][10][11][12]. The Nphenylamides with other aliphatic or aromatic acyl groups (1m-u)a lso workedw ell, affording the corresponding amines (2m-u)i nh igh yield (72-95%)a nd high CÀO/CÀNs electivity (10:1-45:1;e ntries 13-21).…”
mentioning
confidence: 99%